Enhancing perceived digital literacy skills and creative self-concept through gamified learning environments: Insights from a longitudinal study. (2020) - Alt, Dorit; Raichel, Nirit
Highlights: The potential of using gamified learning to increase digital literacy (DL) skills and creative self-concept (CSC) was tested. Data were gathered from two groups: research and control (which has not experienced the intervention), both groups were Education students. Participants' perceived DL skills and creative self-concept were surveyed twice - before (pretest) and after (posttest) a three-month intervention. The students created gamification projects. Results revealed significant differences between the pre/post tests only for the research group on the DL and CSC factors. Abstract: This longitudinal quasi-experimental mixed methods study examined the potential of employing a gamified problem-based learning (hereinafter: the intervention) to increase digital literacy (DL) skills and creative self-concept among undergraduate students. The first step of the study was used to develop and validate an efficient measure of students' perceptions of their DL skills. Step 2 was employed to check the research hypotheses by a quasi-experiment interventional study design. To this end, data were gathered from two groups: research and control (which has not experienced the intervention), both groups were Education students. Participants' perceived DL skills and creative self-concept (CSC) were surveyed twice – before (pretest) and after (posttest) a three-month intervention. Lastly, qualitative data were collected and analyzed (Step 3) to better understand the quantitative data results. Results revealed significant differences between the pre/post tests only for the research group on the DL and CSC factors – the scores at the posttest were higher than the pretest. Non-significant differences were indicated between the tests for the control group. Results also indicated significant low to moderate connections between the DL and CSC factors. The qualitative data analysis revealed four main categories pertaining to DL skills; technology-enabled collaboration; perceived creativity; and transfer of knowledge and skills.